STUDENTS PERCEPTION ON THE USE OF TEXTBOOK FOR ENGLISH LEARNING OF SECOND YEAR STUDENTS OF AS-SHOFA JUNIOR HIGH SCHOOL PEKANBARU - Mulia, Ramlan; Syarfi, M.; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: Textbooks are an essential component of the educational system because they fulfill so many functions. For students, they not only provide as the corpus of knowledge on their grade level, but they also give their learning structure and reinforcement through their organization and illustration (Miller & Berry, 1962). the use of printed books in learning, especially learning English, has several opinions. Books can help teachers explain material according to lesson plans and also help students understand the lessons which delivered by the teacher. This study is looking forward to the students of As-Shofa Junior High School perception’s towards the use of textbook for English learning. The researcher choose descriptive method as design method to collect the data from the students’ perception. The results of the questionnaireadministered to second-year students of As-Shofa Junior High School regarding the use of textbooks for English learning can be categorized as Positive Perception. Out of the total 26 respondents, the questionnaire yielded a percentage of 75.19 out of 100 available points. The highest score is observed in item number 12, addressing whether the English textbook suits students' level due to clear instructions for the grammar and vocabulary parts. This item obtained a score of 117 out of 130 points available, with a percentage of 90%. Conversely, the lowest scoreis attributed to item number 14, concerning the ease of completing exercises in the English textbook with teacher explanation. This item received a score of 53 out of 130 points available, translating to a percentage of 40.77%. This research also finds the teacher to attentively consider and integrate the feedback provided by students into their teaching practices. Hopefully they will build upon the findings to delve deeper into related areas of inquiry, expanding the knowledge base in the field of language educationKey Words: Perception, Textbook, Learning